2021
DOI: 10.21203/rs.3.rs-713339/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adsorption of NO, NO2 on Rh Embedded h-BN Monolayer: A First-Principles Study

Abstract: Density functional theory calculations have been made to investigated the adsorption and sensing properties of harmful nitrogen oxides (NO, NO2) on rhodium (Rh) doped hexagonal boron nitride (BN) to explore the feasibility of Rh-doped BN (Rh-BN) based gas sensor. For each gas molecule, various adsorption positions and orientations were examined. The favorable adsorption configuration has been established and the corresponding adsorption energy has been calculated. Besides, to understand the adsorption mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, many types of research have shown that nanouid can effectively change the wettability of the rock. [23][24][25][26][27][28] Caili Dai et al 29 prepared a new kind of selfdispersing silica nanoparticle and used it to enhance oil recovery in spontaneous imbibition experiments of lowpermeability cores. The excellent performance of nanouids was attributed to the fact that nanouids could signicantly change the wettability of rocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, many types of research have shown that nanouid can effectively change the wettability of the rock. [23][24][25][26][27][28] Caili Dai et al 29 prepared a new kind of selfdispersing silica nanoparticle and used it to enhance oil recovery in spontaneous imbibition experiments of lowpermeability cores. The excellent performance of nanouids was attributed to the fact that nanouids could signicantly change the wettability of rocks.…”
Section: Introductionmentioning
confidence: 99%